Evolution of the technical efficiency of Spanish livestock farming under the Common Agricultural Policy (CAP) (1993 to 2005) = Evolución de la eficiencia técnica de la ganadería española en el marco de la Política Agraria Común (PAC) (1993-2005) (Pecvnia : Revista de la Facultad de Ciencias Económicas y Empresariales, Universidad de León, 2014)
The aim of this paper was to measure the technical efficiency of various sub-sectors of livestock farming in Spain on the basis of information released by the Spanish National Agricultural Accounting Network for the period 1993 to 2005, in order to perform a comparative analysis of these various sub-sectors and to attempt to determine the factors which affected their efficiency. The methodological framework for measuring the efficiency was the stochastic frontier function suggested by Battese and Coelli (1992) and the form chosen for it estimation was a Cobb-Douglas production function. The data base was composed with six variables, thirteen different accounting years and eleven types of livestock farming. The results of estimation indicate that, over the period considered, the efficiency levels decreased. The bovine sub-sector had the worst levels and growth rates, whilst the grain-fed sub-sector had the best results, probably because it is the most integrated.Este artículo tiene como objetivo medir la eficiencia técnica de las Orientaciones Técnico Económicas ganaderas a partir de la información de la Red Contable Agraria Nacional para el período 1993-2005 y realizar un análisis comparativo entre las ramas ganaderas en función de sus niveles de eficiencia. El marco metodológico para medir la eficiencia será la función frontera estocástica propuesta por Battese y Coelli (1992), y la forma funcional elegida para su estimación es una Cobb-Douglas, la base de datos está constituida por un panel de 6 variables, 13 años y 11 orientaciones ganaderas. Los resultados de las estimaciones, indican que a lo largo del periodo los niveles de Eficiencia han disminuido y, del conjunto de orientaciones, son las ramas Bovinas las que presentan menores índices y tasas de variación mientras que las granívoras son las que obtienen los mejores resultados debido a su proceso de integración productiva.